2010
DOI: 10.1016/j.jconrel.2010.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Zero-order controlled release of ciprofloxacin-HCl from a reservoir-based, bioresorbable and elastomeric device

Abstract: A reservoir-based device constructed of a completely biodegradable elastomer can enable many new implantation and insertion options for localized drug therapy, particularly in the case of urological therapies. We performed an in vitro performance evaluation of an implantable, bioresorbable device that supplies short-term controlled release of ciprofloxacin-HCl (CIP). The proposed device functions through a combination of osmosis and diffusion mechanisms to release CIP for short-term therapies of a few weeks du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Elastomers such as PGS have demonstrated exceptional promise for neural tissue engineering applications. [107] PGS can also be fabricated into small diameter tubes, [108] which could have potential applications as biodegradable conduits to enhance peripheral nerve repair. The general lack of observed swelling in synthetic elastomers upon hydration and subsequent degradation would be of particular interest for this application.…”
Section: Neural and Retinal Tissue Engineeringmentioning
confidence: 99%
“…Elastomers such as PGS have demonstrated exceptional promise for neural tissue engineering applications. [107] PGS can also be fabricated into small diameter tubes, [108] which could have potential applications as biodegradable conduits to enhance peripheral nerve repair. The general lack of observed swelling in synthetic elastomers upon hydration and subsequent degradation would be of particular interest for this application.…”
Section: Neural and Retinal Tissue Engineeringmentioning
confidence: 99%
“…Porous PGS scaffolds have been used to support the growth of cardiac tissue [7,8], blood vessels [9,10], and cartilage [11][12][13]. Additionally, PGS has also been used as a degradable drug carrier for antibiotics and anticancer drugs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Formulation F1 prepared using (3:1) gelatin and sodium alginate showed highest percent cumulative drug release while the formulation F2 prepared (1:3) gelatin and sodium alginate showed lowest release at the end of 24 h. The n value obtained from the korsmeyer -peppas kinetic model or curve is known as the release exponent and it indicates the mechanism of drug release [16][17][18]. The value of n for implants formulation was between 0.45 to 0.89 and this indicated that the release mechanism was Anomalous transport mechanism.…”
Section: Discussionmentioning
confidence: 99%